The effects of global real economic crisis on the markets for fossil and renewable fuels - Jobbágy, Péter; Bai, Attila (Applied Studies in Agribusiness and Commerce, 2012)
The 2008/2009 world economic crisis had significant impact on the oil and fuel markets. The crisis developed from the meltdown of American and European mortgage and financial markets and rapidly involved the global real economy. As each country reacted differently to the crisis, the changes in the fuel market also showed significant geographic variation. In our present research, the actions of the US, German and Hungarian fuel markets were analysed for the answer to the reasons for the differences in crisis reactions. We examined the tendency of fuel consumption, the changes of price elasticity for gasoline and diesel and the possible effects of the crisis on the regulatory system.